Highly Efficient and Stable Luminescence from Microbeans Integrated with Cd‐Free Quantum Dots for White‐Light‐Emitting Diodes. (2nd September 2015) - Chen, Wei; Wang, Kai; Hao, Junjie; Wu, Dan; Wang, Shang; Qin, Jing; Li, Chen; Cao, Wanqiang
<x xml:space="preserve">Abstract</x> A high luminous efficiency of quantum dots (QDs) can be attained when incorporating them into mesoporous silica particles by a non‐chemical method. The obtained luminescent microbeads can be dispersed into a polymer by physical blending. Composite films demonstrate a high light‐conversion efficiency, as well as an excellent stability under high‐temperature and high‐humidity conditions.